Quantitative sensory testing in physically active individuals and patients who underwent multidisciplinary pain therapy in the longitudinal course - Dapunt, Ulrike A.; Gantz, Simone; Zhuk, Anastasia; Gather, Katharina Susanne; Wang, Haili; Schiltenwolf, Marcus (Journal of pain research, 2018)
Quantitative sensory testing in physically active individuals and patients who underwent multidisciplinary pain therapy in the longitudinal course Ulrike Dapunt, Simone Gantz, Anastasiya Zhuk, Katharina Gather, Haili Wang, Marcus Schiltenwolf Center for Orthopaedics, Trauma Surgery and Spinal Cord Injury, Heidelberg University Hospital, Schlierbacher Landstrasse, Heidelberg, Germany Objective: The aim of this study was to evaluate possible differences of quantitative sensory testing (QST) results in healthy individuals (group control, n=20), physically active individuals (group sport, n=30) and in patients suffering from chronic musculoskeletal pain (group pain, n=30). Methods: Thermal detection thresholds, thermal pain thresholds and blunt pressure pain thresholds were measured at various sites (T0). Additionally, group pain was treated in multidisciplinary pain therapy for 4 weeks. All groups were retested after 4 weeks to evaluate the reliability of QST measurements and to investigate possible early changes following treatment (T1).Results: Importantly, QST-measurements showed stable test results for group sport and group control at both time points. Athletes demonstrated the highest pain thresholds in general (cold pain threshold mean in degree Celsius for the hand: 5.76, lower back right: 7.25, lower back left: 7.53; heat pain threshold mean in degree Celsius for the hand: 46.08, lower back right: 45.77, lower back left: 45.70; and blunt pressure pain mean in kilograms for the hand: 3.54, lower back right: 5.26, lower back left: 5.46). Patients who underwent therapy demonstrated significant differences at T1 (cold pain threshold hand mean in degree Celsius for the hand: 11.12 [T0], 15.12 [T1]; and blunt pressure pain mean in kilograms for the lower back right: 2.87 [T0], 3.56 [T1]). They were capable of enduring higher blunt pressure, but on the other hand cold pain tolerance had decreased (P=0.045 and P=0.019, respectively).Conclusions: In conclusion, we were able to demonstrate significant differences of QST results among the three groups and we detected early changes following multidisciplinary pain therapy, which will be discussed. Keywords: quantitative sensory testing, chronic musculoskeletal pain, multidisciplinary pain therapy
Gesehen am 09.12.2019